Public Participation in Elections - Rahmat Hidayat; Luqman Abdulhakim; Yusran Sibawaih; Muh. Rajib (Trescode Green Organization, 2025)
In every election, community participation is an interesting thing to study and discuss, the history of the long journey of elections from 2004 to 2024 elections is a form of evidence of the ups and downs of community participation, this is due to many factors and it is the duty of election organizers to evaluate this. This research was conducted to examine and want to know how the urgency of community participation in elections and how the strategies of election organizers in strengthening community participation using library research, namely research material obtained from library materials related to the object under study. The urgency of community participation in elections can have a significant impact on the stability of democracy, this is based on the fact that a country that adheres to a democratic system is obliged to involve its people, with low participation rates resulting in unhealthy democratic stability, besides the urgency of community participation in elections can guarantee legitimacy in the government order. So to maintain the stability of democracy and the legitimacy of the government requires the role of election administrators, namely the KPU and Bawaslu, the movements that can be carried out by the KPU are conducting political education, socialising elections and providing assistance to disability elections, while the movement that can be carried out by Bawaslu is to provide space for the community to participate in election supervision in order to achieve participation and peaceful and honest elections.